Adaptation of Belk’s materialism scale to the Polish population and assessment of relationships between materialism, values, religiosity, and pro-environmental beliefs - Uram, Patrycja (Journal of beliefs and values, 2025)
According to Russell Belk’s conceptualisation, materialism is a personality trait reflected in possessiveness, envy, and non-generosity. The aim of the study was to adapt Belk’s Materialism Scale (BMS) to the Polish population, specifically, to evaluate its psychometric properties (factor structure and reliability) and convergent and divergent validity. Also, we aimed to examine relationships between materialism and values (according to Schwartz’s theory), religiosity, and pro-environmental beliefs (within the New Ecological Paradigm). We conducted two studies: the adaptation study I (N = 770) and the hypotheses-testing study II (N = 568). In Study I, we performed confirmation and exploration factor analyses (CFA and EFA) and established a convergent validity (with the Richins & Dawson’s Materialism Value Scale) and a discriminant validity (with the Jaworska-Gruszczyńska’s Time Organization Scale). After modifying the initial model of the materialism scale, based on error covariance and changes in the number of items, we developed the Polish version of the BMS, which proved its applicability in the Polish population. The Study II results showed that materialism positively related to self-enhancement value, while it negatively related to openness to change and self-transcendence values, and religiosity. In this study, we developed a Polish version of Belk’s Materialism Scale and assessed the relationship between values, materialism (a personality trait), religiosity, and environmentalism. Our results indicated that differences in materialism might underlie the relationship between values and pro-environmental attitudes.